Features of organizing public-private partnerships in the implementation of high-tech projects - M. Ya. Veselovsky; D. D. Levteev (Vestnik of Samara State University of Economics, 2026)
This article examines the specifics of public-private partnerships (PPPs) as they relate to hightech projects of strategic importance for regional and industry development. PPPs can drive technological progress, stimulating the creation of new jobs, increasing labor productivity, and improving the quality of life. The article analyzes the challenges and limitations associated with the specific nature of such projects, including high investment risks, long payback periods, the need for regular upgrades of assets and technologies, a shortage of qualified personnel, and complex regulatory frameworks. Particular attention is paid to tools and mechanisms that help mitigate risks for private investors and ensure effective government participation in projects. Global practices and current methodological approaches to the development and implementation of public-private partnership projects in high-tech industries are examined, and recommendations for adapting them to Russian business conditions are offered. The paper also examines the development of an optimal model for interaction between participants in PPP projects, including the distribution of responsibilities, risk management, and coordination of all stakeholders. The article is intended for specialists in economics, public administration, and innovation policy.